1998
DOI: 10.1677/jme.0.0200233
|View full text |Cite
|
Sign up to set email alerts
|

Binding characteristics of antibodies to the TSH receptor

Abstract: We have used fragments of the TSH receptor (TSHR) expressed in E. coli as glutathione S-transferase fusion proteins to produce rabbit polyclonal antibodies and a panel (n=5) of monoclonal antibodies to the extracellular fragment of the TSHR. The binding characteristics of the antibodies to linear, conformational, glycosylated and unglycosylated forms of the receptor in different assay systems have been investigated.The reactivity of these antibodies with the TSHR was assessed by Western blotting with both nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 45 publications
(39 reference statements)
1
26
0
1
Order By: Relevance
“…Intact IgG was undetectable by SDS-PAGE in the Fab preparations. mAb IgG and Fab preparations were labelled with 125 I as described previously (22). labeled TSH binding to TSHR-coated tubes (kit from RSR Ltd, Cardiff, United Kingdom) (23) (inhibition range 11%-98%).…”
Section: Production and Labeling Of Mabsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intact IgG was undetectable by SDS-PAGE in the Fab preparations. mAb IgG and Fab preparations were labelled with 125 I as described previously (22). labeled TSH binding to TSHR-coated tubes (kit from RSR Ltd, Cardiff, United Kingdom) (23) (inhibition range 11%-98%).…”
Section: Production and Labeling Of Mabsmentioning
confidence: 99%
“…In addition, assays using Chinese hamster ovary (CHO) cells expressing hTSHR (approximately 50,000 receptors per cell) (22) were carried out according to the method of Latif et al (27). Briefly, CHO cells were seeded into 96-well plates (30,000 cells per well) and incubated for 24 hours in Dulbecco's modified Eagle's medium (DMEM) (Invitrogen Ltd., Paisley PA4 9RF, UK) containing 10% fetal calf serum.…”
Section: Analysis Of Mab Thyroid Stimulating Activitiesmentioning
confidence: 99%
“…Concentrations of hamster mAb used were saturating unless otherwise indicated. Monoclonal TSHR-Abs M1 and M4, used in our cleavage assay, were mouse IgG 1 (Oda et al 1998(Oda et al , 2000 kindly supplied by Dr B Rees Smith (RSR Limited, Cardiff, UK). 2C11 was a mouse IgG 1 TSHR-mAb (Shepherd et al 1999) purchased from Serotec (Raleigh, NC, USA).…”
Section: Cells and Tshr-mabsmentioning
confidence: 99%
“…Recombinant human TSHR expressed in CHO-K1 cells (4 3 10 5 TSHR per cell as assessed by Scatchard analysis of TSH binding) were isolated, solubilized with 50 mM NaCl, 10 mM Tris-HCl pH 7.5, 1% Triton-X-100, and centrifuged (90000g for 2 hours at 4°C) as previously described (9). TSHR mouse monoclonal antibody (3F3 IgG; [9]) was coupled to CNBr-activated sepharose 4B (Amersham Pharmacia Biotech, St. Albans, UK) and the gel packed into a column.…”
Section: Tshr Preparationsmentioning
confidence: 99%
“…Recombinant TSHR produced in Chinese hamster ovary (CHO) cells and extracted with detergents is usually present in two main forms: a 100-kd precursor form consisting of the full-length 84-kd peptide chain and high mannose sugar residues and a 120-kd mature form consisting of the fulllength peptide chain and complex-type sugars (7)(8)(9)(10)(11). Recent studies have shown that only the 120-kd form of the TSHR is principally responsible for binding TSH and we now describe a study of the interaction of TRAb with the two forms of the receptor.…”
Section: Introductionmentioning
confidence: 99%